Effect of nanosized Mg0.6Ni0.4O prepared by self-propagating high temperature synthesis on sulfur cathode performance in Li/S batteries - Zhang, Yongguang; Bakenov, Zhumabay; Zhao, Yan; Konarov, Aishuak; Doan, The Nam Long; Sun, Kyung Eun Kate; Yermukhambetova, Assiya; Chen, P. (Powder Technology, 2013)
Abstract Nanostructured magnesium nickel oxide Mg0.6Ni0.4O was successfully synthesized by self-propagating high temperature synthesis (SHS) followed by heat treatment. The effect of the precursor composition and calcination temperature on the Mg0.6Ni0.4O powder properties was investigated. These particles were used as an additive to prepare S/Mg0.6Ni0.4O composite via ball-milling with sulfur. The composite preparation conditions were optimized to achieve the higher specific surface area without compromising the sample crystallinity. The SEM observation revealed that the sulfur morphology was drastically changed by the Mg0.6Ni0.4O addition, from smooth to rough agglomerated particles. This change has enhanced the electrochemical performance of the composite cathode. Cyclic voltammetry and charge–discharge tests demonstrated enhanced reversibility and high sulfur utilization in a Li/S cell with S/Mg0.6Ni0.4O cathode, delivering about 850mAhg−1 of reversible capacity at the initial cycle. The effect of the Mg0.6Ni0.4O heat treatment temperature on the S/Mg0.6Ni0.4O cycling performance was also investigated. The cathode with Mg0.6Ni0.4O calcined at 700°C exhibited enhanced capacity retention which could be due to its high specific surface area and nanosized structure.
Keywords: Self-propagating high temperature synthesis; Mg0.6Ni0.4O; Sulfur cathode additive; Lithium–sulfur battery